Analysis of the utilization degree of deformation work in drawing processes (Journal of Production Engineering, 1984)
The work provides a computer analysis of the influence of certain process parameters on the degree of utilization of the deformation work, as well as a comparison with the influence of these parameters on the formability of the material.
Keywords: computer analysis; deformation; drawing processes